The genus Erythraeus (Acari: Erythraeidae) from China with descriptions of two new species and a key to larval species of the genus worldwide - Xu, Si-Yuan; Yi, Tian-Ci; Guo, Jian-Jun; Jin, Dao-Chao (Zootaxa, 2019)
Two new mite species, Erythraeus (Erythraeus) hubeiensis sp. nov. and E. (Zaracarus) hainanensis sp. nov., are described and illustrated based on larvae parasitizing insects (Hemiptera) in Hubei and Hainan Provinces, China. An updated key to larval species of the genus Erythraeus of the world is presented.